Stimulasi Tunas Adventif sebagai Bahan Perbanyakan Vegetatif pada Labu Madu Hibrida - Putri Maya, Cintiya Dwi; Juhan, Muhammad (JURNAL AGROPLANT, 2023)
Hybrid honey gourd is an exclusive commodity because of its fruit shape, appearance, nutritional content, benefits and also the high price. Cultivation of hybrid honey gourd is not too difficult, one of the problems is the procurement of expensive seeds. This can be overcome by vegetative propagation using adventitious shoots which are usually removed. In research, innovations emerged to stimulate adventitious shoots to be successfully developed for vegetative propagation. This study aims to obtain a hybrid honey pumpkin vegetative propagation method, to describe the growth and development of honey pumpkin seeds from vegetative propagation. The design used was a factorial 3x3 randomized block design (RAK) with 3 replications. The first factor is the internode position of the shoot (D) which consists of three segments (D1); four segments(D2); five segments (D3). The second factor is a stimulant (S) consisting of 6 grams of pearl NPK fertilizer per one liter of water combined with 1.5 ml atonic atonic (S1); 3 ml (S2); 4.5 ml (S3). In total there were 9 treatments, namely D1S1, D1S2, D1S3, D2S1, D2S2, D2S3, D3S1, D3S2, D3S3. The collected data were analyzed by analysis of variance and F-test if significantly different, followed by the DMRT 5% test. Inter-unit parameters in one individual (section length) were analyzed by student's t-test.